STRATEGI KOMUNIKASI PEMASARAN RRI MALANG DALAM PENINGKATAN JUMLAH PENGIKLAN - Yosadak Sosten Olla; Ellen Meianzi Yasak (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: The purpose of this study is (1) to determine the marketing communications strategy implemented by RRI Malang in an increasing number of advertisers; (2) to determine the factors that affect the marketing communication strategy on Radio Repubik Indonesia in an increasing number of advertisers. The results showed that the efforts of Radio Republik Indonesia of Malang in increasing the number of advertisers through advertising, personal selling, sales promotion, direct selling, publicity and public relations by using the concept of AIDDA in the marketing system. The study also found several factors that support and hinder the marketing communication strategy has been planned. The supporting factors, among others for Radio Republik Indonesia Malang belonging to the media group that has a big name among the community. So that it can open up opportunities as possible to establish cooperation with other parties. In the end clients who are satisfied with the services provided advertise continuously. As well as the Radio Republik Indonesia brought the concept of the unique and different from the radio in general for Czech Radio Malang based on wisdom. Whereas the inhibiting factor is the limitations of the HR (Human Resources) owned by Radio Republic of Indonesia in Malang, employees who do not qualify because of the uncertainty the number of links, customer satisfaction as well as tough competition with other radios. Keywords: Communication Strategy Marketing, Advertising Abstrak: Tujuan penelitian ini adalah (1) untuk mengetahui strategi komunikasi pemasaran yang diterapkan oleh RRI Malang dalam peningkatan jumlah pengiklan; (2) untuk mengetahui faktor-faktor yang mempengaruhi strategi komunikasi pemasaran pada Radio Repubik Indonesia dalam peningkatan jumlah pengiklan. Hasil penelitian menunjukkan bahwa upaya Radio Republik Indonesia Malang dalam meningkatkan jumlah pengiklan melalui advertising, personal selling, sales promotion, direct selling, publicity dan public relation dengan menggunakan konsep AIDDA dalam system marketing. Penelitian ini juga menemukan beberapa factor yang mendukung serta menghambat strategi komunikasi pemasaran yang telah direncanakan. Faktor pendukung antara lain karena Radio Republik Indonesia Malang tergabung dalam media Group yang mempunyai nama besar dikalangan masyarakat. Sehingga dapat membuka peluang sebesar-besarnya untuk menjalin kerjasama dengan pihak lain. Pada akhirnya klien yang merasa puas atas pelayanan yang diberikan memasang iklan secara kontinu. Serta Radio Republik Indonesia mengusung konsep unik serta berbeda dari radio pada umumnya karena Radio Republik Malang berlandaskan kearifan. Sedangkan factor penghambatnya yaitu keterbatasan SDM (Sumber Daya Manusia) yang dimiliki oleh Radio Republik Indonesia di Malang, karyawan yang belum memenuhi kualifikasi, tidak menentunya jumlah sponsor, kepuasan konsumen serta persaingan ketat dengan radio lain. Kata Kunci: Strategi Komunikasi Pemasaran, Iklan